The UN Framework Convention on climate change and judicial policies of domestic courts - Alexander Shytov (2018)
© Common Ground Research Networks, Alexander Shytov All Rights Reserved. The recent changes in environmental laws of such Asian countries like China, Thailand, and Vietnam provide their courts with the extensive powers to protect the environment. The judiciary within the national political institutions of many Asian countries now has sufficient legal powers to apply the general principles of the UN Framework Convention on Climate Change (UNFCCC) when interpreting and enforcing their domestic laws. The recent developments of judicial policies in a number of Asian countries indicate that the courts are more willing to take general environmental considerations seriously. However, these powers have not been used so far to control greenhouse gas emissions due to a number of political and cultural influences. The paper will examine the challenges which stand before the courts in a number of Asian countries to enforce international law on Climate Change.